2016
DOI: 10.1016/j.mimet.2016.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Differential recognition of the multiple banded antigen isoforms across Ureaplasma parvum and Ureaplasma urealyticum species by monoclonal antibodies

Abstract: Two separate species of Ureaplasma have been identified that infect humans: Ureaplasma parvum and Ureaplasma urealyticum. Most notably, these bacteria lack a cell wall and are the leading infectious organism associated with infection-related induction of preterm birth. Fourteen separate representative prototype bacterial strains, called serovars, are largely differentiated by the sequence of repeating units in the C-terminus of the major surface protein: multiple-banded antigen (MBA). Monoclonal antibodies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Variations in the size of the MBA lipoprotein, modulates the host immune response [376]. MBAs from different ureaplasma species are different and respond to different antibodies as well [377]. In HeLa cells in culture, it has been observed that Ureaplasmas enter the cells through clathrin-mediated endocytosis after binding of the pathogen by sulfoglycolipids membrane receptors [378].…”
Section: Placentamentioning
confidence: 99%
“…Variations in the size of the MBA lipoprotein, modulates the host immune response [376]. MBAs from different ureaplasma species are different and respond to different antibodies as well [377]. In HeLa cells in culture, it has been observed that Ureaplasmas enter the cells through clathrin-mediated endocytosis after binding of the pathogen by sulfoglycolipids membrane receptors [378].…”
Section: Placentamentioning
confidence: 99%